Spatial Analysis of Healthcare Facility Accessibility Using GIS (Case Study: Pantai Labu Subdistrict, Deli Serdang Regency) - Novida Yenny; Riki Rahmad; Mulhady Putra; Mona Adria Wirda; M. Rizky Pratama Ginting (Jurnal Mamangan, 2026)
Healthcare accessibility is a central pillar of Universal Health Coverage (UHC), yet spatial inequities persist in many coastal and semi-rural regions due to uneven facility distribution, limited transport connectivity, and infrastructural vulnerability. This study evaluates the spatial accessibility of primary healthcare services in Pantai Labu Subdistrict, North Sumatra, Indonesia, using an integrated Geographic Information System (GIS) framework. The analysis combines Euclidean buffer analysis, road proximity assessment, and network-based accessibility modeling to capture both theoretical and functional dimensions of access. Results reveal pronounced central–peripheral disparities: while most settlements fall within the administrative service radius of the main Puskesmas and its auxiliary Puskesmas Pembantu (Pustu), effective accessibility remains constrained in coastal and inland fringe areas due to weak road connectivity and linear transport dependence. The inclusion of Pustu facilities reduces distance-based gaps; however, functional limitations, particularly the uneven implementation of Integrated Primary Care (ILP) undermine service utilization in several spatially accessible locations. Network analysis further demonstrates that buffer-based methods systematically overestimate accessibility, failing to account for indirect routing, corridor dependence, and cross-boundary healthcare use. Underserved settlements persist where distance, road isolation, and limited service capacity converge, forming localized access deserts despite formal coverage compliance. The study concludes that equitable healthcare access in coastal semi-rural settings requires integrated planning that aligns facility functionality with resilient transport infrastructure. The proposed GIS-based framework offers a replicable, policy-relevant tool for identifying priority intervention zones and supporting spatially targeted strategies to advance UHC in vulnerable regions.